(untitled) (Journal of actual problems of jurisprudence, 2018)
This article describes the main ideas concerning the form of government in the Republic of Kazakhstan. It is noted that the presidential form of government best reflects the hopes and aspirations of the Kazakh people. It is proved that the constitutional provisions concerning the inviolability of tenure and form of government of Kazakhstan aimed at maintaining the stability of the Republic of Kazakhstan. Key words: The Republic of Kazakhstan, President, form of government, a presidential republic, the Constitution, the leader of the nation.